Determinasi Literasi Asuransi Syariah Generasi Z: Peran Digital Marketing, Religiusitas, dan Budaya Sosial di Sumatera Barat - Adisti, Adila; Chairunnisya, Chairunnisya; Al Iffah, Nisa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
The Islamic insurance industry plays a strategic role in the financial system; however, its utilization in Indonesia remains relatively low. This condition is particularly critical for Generation Z, who will become the dominant users of financial products in the future. This study aims to analyze the effects of digital marketing, religiosity, and social culture on Sharia insurance literacy among Generation Z in West Sumatra Province. The study employs a quantitative approach with an explanatory research design and utilizes the SEM-PLS method, based on data from 201 respondents aged 17–27 years collected. The results indicate that social culture and digital marketing have a positive and significant effect on Sharia insurance literacy, while religiosity does not have a significant direct effect. The research model explains 39.1% of the variation in Sharia insurance literacy, highlighting the important role of social and digital factors in shaping Sharia insurance literacy among Generation Z.